Pengaruh Nilai Perusahaan dan Financial Distress terhadap Harga Saham dengan Struktur Modal sebagai Moderasi - Tanjung, Oktami Nabella; Sarlawa, Rita; Widyaningsih, Dhina Sri; Hamzah, Pratiwi (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
This study is grounded in the volatility of LQ45 stock prices on the Indonesia Stock Exchange (IDX) during 2020–2024, influenced by global economic dynamics and post-pandemic conditions. This study aims to examine the impact of firm value and financial distress on stock prices, as well as to explore the role of capital structure as a moderating variable. The study employs a quantitative method with secondary data sourced from corporate financial reports. Purposive sampling technique yielded 9 companies with 45 observations. Data processing was conducted through PLS-SEM combined with Moderated Regression Analysis (MRA). The findings reveal that firm value has a positive and significant effect on stock prices (T-statistic = 5.912; p = 0.000), suggesting that higher company valuation leads to greater investor appreciation. In contrast, financial distress shows no significant effect on stock prices (β = 0.002; p = 0.990), as financial distress information for large-cap LQ45 issuers is already priced in early by investors. Capital structure successfully moderates the relationship between firm value and stock prices (T-statistic = 2.495; p = 0.013), indicating that an optimal financing composition strengthens the positive signal of firm value in the market. However, capital structure fails to moderate the impact of financial distress on stock prices (β = −0.189; p = 0.261), suggesting that market sentiment and external factors dominate stock price movements under financial pressure conditions. The overall model explains 55.1% of stock price variation. These results indicate that corporate financing decisions are more dominated by firm value and capital structure than by financial distress risk. This study provides managerial implications for investors and corporate management in designing increasingly accurate and strategic financial policies to enhance firm value and stock price stability in the capital market.